2013
DOI: 10.1177/1094670513494015
|View full text |Cite
|
Sign up to set email alerts
|

Managing Engagement Behaviors in a Network of Customers and Stakeholders

Abstract: Firms striving for long-term profitability need to build stronger customer-firm relationships by getting their customers more engaged with the firm. One path to this end is introducing practices to manage different forms of customer engagement behaviors (CEBs). To develop more effective and efficient CEB management practices, this research proposes and empirically tests a theoretical model on managerial and psychological processes to encourage CEBs that are embedded in a broader network of customers and stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
320
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(336 citation statements)
references
References 58 publications
10
320
0
6
Order By: Relevance
“…While early engagement research adopted a predominant focus on online contexts, including social media (e.g. Brodie et al, 2013), a recent shift is observed towards the examination of engagement in offline contexts, including retail settings (Vivek et al, 2012), tourism services (So et al, 2014), nursing homes (Verleye, Gemmell, & Rangarajan, 2014) and public transportation services (Jaakkola & Alexander, 2014). In commentaries at the conclusion of this special issue (Calder, Malthouse, & Maslowska, 2016;Hollebeek et al, 2016), further elaboration on key observed trends in recent engagement research is provided, along with the development of an engagement-based future research agenda.…”
Section: Strategic Drivers Anticipated and Unanticipated Outcomes Ofmentioning
confidence: 99%
“…While early engagement research adopted a predominant focus on online contexts, including social media (e.g. Brodie et al, 2013), a recent shift is observed towards the examination of engagement in offline contexts, including retail settings (Vivek et al, 2012), tourism services (So et al, 2014), nursing homes (Verleye, Gemmell, & Rangarajan, 2014) and public transportation services (Jaakkola & Alexander, 2014). In commentaries at the conclusion of this special issue (Calder, Malthouse, & Maslowska, 2016;Hollebeek et al, 2016), further elaboration on key observed trends in recent engagement research is provided, along with the development of an engagement-based future research agenda.…”
Section: Strategic Drivers Anticipated and Unanticipated Outcomes Ofmentioning
confidence: 99%
“…The CEB literature proposes that customers can have different motives to engage in these behaviors (Jaakkola and Alexander, 2014;van Doorn et al, 2010). Moreover, customers can target different actors (e.g., the firm, its employees, other customers) with CEBs (e.g., Brodie et al, 2011;Verleye et al, 2014). From the aforementioned description, CEBs overlap with customer voluntary performance (CVP) and customer citizenship behaviors (CCBs), which are defined as, respectively, "helpful, discretionary behaviors of customers that support the ability of the firm to deliver service quality" (Bettencourt, 1997, p. 384) and "voluntary and discretionary behaviors that are not required for the successful production and/or delivery of the service but that, in the aggregate, help the service organization overall" (Groth, 2005, p. 11).…”
Section: Different Forms Of Customer Engagement Behaviorsmentioning
confidence: 99%
“…Consider, for example, new product and service development platforms (e.g., www.MyStarbucksIdea.com, where customers can post new product and service ideas), reward programs (e.g., Bank of America paying customers for referrals), and customer communities (e.g., Weight Watchers meetings, in which people give and get advice on losing weight) (Brodie et al, 2011;Park et al, 2013;Verleye et al, 2014). In these examples, firms encourage customers to show engagement behaviors, such as giving feedback, spreading positive word of mouth, or helping other customers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a literature review and in-depth interviews with Senior Executives of free e-service providers, the authors present a typology of non-monetary value contributions in the free e-service sector, which includes word-ofmouth, co-production, and network value effects arising from non-paying customers. In the second paper titled 'Capturing Value from Non-Paying Consumers' Engagement Behaviours: Field Evidence and Development of a Theoretical Model' Groeger, Moroko and Hollebeek develop a taxonomy of non-paying customer engagement behaviours and ways in which these may generate customer value by drawing on a mixed methods approach and two field studies, thereby extending the work of van Doorn et al (2010), Hollebeek (2012), Jaakkola and Alexander (2014), and Verleye, Gemmel, and Rangarajan (2014).…”
mentioning
confidence: 99%